20 million pregnant women with group B streptococcus carriage: consequences, challenges, and opportunities for prevention. Issue 2 (16th April 2023) - Paul, Proma; Gonçalves, Bronner P.; Le Doare, Kirsty; Lawn, Joy E.
Abstract : Purpose of review: Intrapartum antibiotic prophylaxis (IAP) is currently the only recommended preventive approach against clinical consequences of maternal Group B Streptococcus (GBS) colonization. In this review, we discuss new findings of total perinatal GBS burden and relative effectiveness of differing targeting of IAP, notably microbiology-based and risk factor-based screening, including potential limitations. Finally, we provide updates on maternal GBS vaccines and their potential cost-effectiveness in disease reduction. Recent findings: Updated estimates of the burden of GBS related to pregnancy outcomes show (1) early-onset GBS disease incidence and deaths are high in some low- and middle-income countries where IAP has not been implemented and (2) late-onset GBS disease, preterm birth, and stillbirth, which are not preventable by IAP, remain a public health problem in both high and low-middle income settings. Observational evidence indicates that microbiology-based screening may be more effective than risk factor-based screening, but even in high-income countries, compliance is imperfect. To address the need for alternative prevention strategies, several maternal vaccine candidates are in clinical development, and modelling suggests these could be cost-effective in most scenarios. Summary: Recent progress in GBS vaccine research holds promise of reducing the large and preventable burden of mortality and disability caused by GBS disease, especially in higher-burden settings where clinical and laboratory services may be limited. Importantly vaccines also hold potential to prevent GBS stillbirths and GBS-associated preterm births.